DESKRIPSI PENGETAHUAN IBU HAMIL TENTANG KEKURANGAN ENERGI KRONIS DI PUSKESMAS PONRE, KECAMATAN GANTARANG, KABUPATEN BULUKUMBA - Husnul Khatimah; Arfiani; Eka Hastuti; Kurnia Septi Ariska (Journal Of Midwifery And Nursing Studies, 2020)
Ponre Public Helath as one of the puskesmas located in Gantarang Subdistrict, Bulukumba Regency, is a Puskesmas with a fairly high number of KEK cases. Based on data from Puskesams Ponre, Gantarang District, Bulukumba Regency, in 2019, January-November, there were 692 pregnant women with 73 KEK cases. This study was to describe the knowledge of pregnant women about chronic energy deficiency at the Ponre Health Center, Gantarang District, Bulukumba Regency. This research is descriptive quantitative. The population in this study were 30 pregnant women and the sample size was the same as a population of 30 pregnant women, with the sampling technique using side totals. The research instrument used was a questionnaire. The knowledge of respondents in the good category were 15 respondents (50.0%), in the sufficient category as many as 13 respondents (43.3%), in the less category as many as 2 respondents (6.7%). Conclusion: the knowledge of pregnant women about KEK in Ponre Puskesmas, Gantarang District, Bulukumba Regency was the most in the good category, namely as many as 15 respondents (50.0%).